Prevalence of insulin resistance and its association with metabolic syndrome criteria among Bolivian children and adolescents with obesity - Rodriguez Susana; Teran Carlos G; Caceres Margoth; Medina Marcos (BMC, 2008)
Abstract Background Obesity is a one of the most common nutritional disorder worldwide, clearly associated with the metabolic syndrome, condition with implications for the development of many chronic diseases. In the poorest countries of Latin America, malnourishment is still the most prevalent nutritional problem, but obesity is emerging in alarming rates over the last 10 years without a predictable association with metabolic syndrome. The objective of our study was to determine the association between insulin-resistance and components of the metabolic syndrome in a group of Bolivian obese children and adolescents. The second objective was determining the relation of acanthosis nigricans and insulin-resistance. Methods We studied 61 obese children and adolescents aged between 5 and 18 years old. All children underwent an oral glucose tolerance test and fasting blood sample was also obtained to measure insulin, HDL, LDL and triglycerides serum level. The diagnosis of metabolic syndrome was defined according to National Cholesterol Education Program-Adult Treatment Panel (NCEP-ATP III) criteria adapted for children. Results Metabolic syndrome was found in 36% of the children, with a higher rate among males (40%) than females (32.2%) (p = 0.599). The prevalence of each of the components was 8.2% in impaired glucose tolerance, 42.6% for high triglyceride level, 55.7% for low levels of high-density lipoprotein cholesterol, and 24.5% for high blood pressure. Insulin resistance (HOMA-IR > 3.5) was found in 39.4% of the children, with a higher rate in males (50%) than females (29%). A strong correlation was found between insulin resistance and high blood pressure (p = 0.0148) and high triglycerides (p = 0.002). No statistical significance was found between the presence of acanthosis nigricans and insulin resistance. Conclusion Metabolic syndrome has a prevalence of 36% in children and adolescent population in the study. Insulin resistance was very common among children with obesity with a significant association with high blood pressure and high triglycerides presence.